A New Route to N1-Substituted Uracil Derivatives Using Hypervalent Iodine - Yoshimura, Yuichi; Kan-no, Hiroya; Kiran, Y. B.; Natori, Yoshihiro; Saito, Yukako; Takahata, Hiroki (Synthesis, 2012)
In continuation of our previous study, oxidative coupling reactions of uracil with allylsilane or enol ethers were examined using diacetoxyiodobenzene. The reaction of persilylated uracil with 3,4-dihydro-2H-pyran in the presence of TMSOTf and PhI(OAc)2 resulted in the formation of a dihydropyranyluracil derivative, although the yield was low. In an extension of the oxidative coupling reaction, a novel glycosylation reaction using glycal derivatives as substrates was also developed. The treatment of persilylated uracil and 3,4-dihydro-2H-pyran with (PhSe)2 and PhI(OAc)2 in the presence of a catalytic amount of TMSOTf gave a 2,3-anti-derivative of 1-(3-phenylselanyltetrahydropyran-2-yl)uracil stereoselectively and in good yield.
Keywords: hypervalent iodine; nucleoside; oxidative coupling; glycosylation; glycal